PENERAPAN PENDEKATAN SCIENCE TECHNOLOGY AND SOCIETY (STS) DALAM PEMBELAJARAN SAIN DI MI - Wibowo, Agus Mukti (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
Model, strategy or approach, which applied in teaching, can influence the process of learning. It assumed that the right approach can increase the ability of students in understanding the concepts which are studied. Generally, the teaching in MI has different characteristic from the elementary school. Creativity or modification model approaches needed to apply the teaching and learning of science in MI. One of the applicable approaches in science teaching, which is appropriate with MI characteristic, is STS. The implementation of STS approach has the opportunity to bring the Islamic teachings such as moral-ethic.Keyword: Approach, concept, STS